Mapping Opportunities to Increase Productivity in Coastal Bangladesh - Chandna, Parvesh Kumar; Nelson, Andrew; Khan, Mohammed Zahirul Haque Khan; Hossain, Mohammed Moqbul; Rana, Md. Sohel; Rashid, Fazlur; Mondal, Manoranjan K.; To Phuc Tuong (International Rice Research Institute, 2014)
The Ganges Basin Development Challenge (GBDC) Program of the CGIAR Challenge Program for Water and Food is focusing on improving livelihoods and increasing productivity sustainably in the coastal polder zone, and has developed and tested innovative cropping systems and water management practices suited to the local conditions.Before a new cropping system can be recommended, it is important to identify its “extrapolation domain,” which determines where it could be successful.